Cultuurhistorie en ruimtelijke kwaliteit van de historische binnenstad. Het geheugen van een straat als inspiratiebron (Bulletin KNOB, 2008)
Until recently cultural planning was a term used to refer to a relatively new field of policy that had come into vogue since the Belvedere Policy Document. Since the Spatial Planning Memorandum (2006) this term has been deleted from policy idiom and replaced by the term 'spatial quality’.The term cultural planning and now spatial quality is regarded as the universal remedy brought forward from the Belvedere point of view since 1999. But does a workable framework providing insight into an integral vision actually exist? It requires more than just a joint motto (conservation through development) and also more than joint projects.In the first place, it requires that the worlds of cultural history and of the planners and designers communicate with each other in an unambiguous manner. As pointed out before, the concept of cultural history is a rather vague and defenceless concept without any formulation of the problems.If we add up the gaps and lacks, there is too little attention on either side for the totality of objects and occurrences of acting man on the level of the historical town centre. Even though a house, a street or a building block has been torn down and even though the residents have moved or died, there is still a memory that may be the basis of a recollection related to such a place, such a building location. The odd thing is that archaeological traces - usually destroyed because of a new building plan - may demonstrate this quite concretely, while historical sources are also present, but all too often remain invisible.The added value of multidisciplinary research into a historical town centre chiefly lies in relating research into the spatial-physical aspect on the one hand to the social-cultural aspect on the other. By linking this to a long-term perspective as well, more insight will be gained into the stratification and the various speeds at which processes are taking place. In addition, the step between research and design should also get more attention.Consequently, the most important recommendations are relatively simple and refer to two things. In the first place, it concerns professionals, so both from the world of cultural history and from spatial planning, who wish to start the discussion on tradition and renovation in a historical town centre. In this respect it is crucial that both the spatial-physical aspect and the social-cultural aspect are taken into consideration and combined as much as possible, for they cannot exist independently. Obviously, this requires much effort from researchers, designers and more attention should be paid to it, notably in current training.In the second place, this discussion should also get a formal context. In my opinion this can best be done by including a cultural-historical paragraph in the zoning plan by means of which cultural-historical research - at any rate in protected village and urban conservation areas - can be enforced if building permits and demolition permits are at issue. By analogy with archaeology legislation this multidisciplinary research should also acquire a legal basis.